Prirastoslovne značilnosti jelke (Abies alba Mill.) v Sloveniji - Kadunc, Aleš (Gozdarski vestnik, 2010)
The aim of this paper is to establish site productivities of Silver fir (Abiesalba Mill.) stands, to show some growth characteristics and to analyze the quality structure of Silver fir trees. The research was carried out on 14 site units. On each, 5 research plots in mature, compact stands where Silver fir dominated were set. Site productivity decreases with the altitude and stoniness while being higher on the concave sites and on the shady or east wards exposed positions. Silver firs from the analyzed stands regenerated in periods lasting 5-70 years. The height and diameter increments are still decreasing after the increment depression in years 1960-1990 on the majority of the sites. The overtopped Silver firs are 10-40 years younger than the dominant ones. The differences are lower on the less productive sites. The assortment structure of Silver fir is more favorable on Silver fir (noncarbonated) sites, partially also on beech sites, while the dinaric Silverfir-beech stands showed the worst structure. The value of the Silver firstems depends to a very large extent on the diameter at breast height, while crown size or crown isolation, forking and site productivity have little effect.
Keywords: forestry; gozdarstvo; gozdovi; produkcijska sposobnost rastišč; sortimentna struktura; pomladitvena doba; jelka; Abies alba Mill.; Slovenia; Slovenija